La recuperación de las relaciones transfronterizas entre los valle de Ansó y Roncal como modelo de colaboración para el futuro - Gorría Ipás, Antonio Jesús (Geographicalia, 2014)
Pyrenean area is characterized by its great diversity, both physically and socio-economic and cultural. For centuries, the exploitation of natural resources (pasture, water, forest... ) led to conflicts between communities, regardless of water slope, region or country. Just the regulation of these exploitations led to links between the valleys, trying to overcome conflicts. Thereby interrelationships were created that comoperatedas integrated spaces. Different political processes and especially lifestyles changes and traditional resource assessment favoured the distance, gaining strength the border concept over a physical social, cultural and economic concept. In recent years, due to EU policies, new frameworks for cooperation were created and eventually the “worldbehind” concept was overcome and again gaining strength common projects in the development and management of resources, moving forward to and more integrated space.